2022
DOI: 10.3350/cmh.2022.0060
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models of hepatocellular carcinoma recurrence after liver transplantation: A comprehensive review

Abstract: Liver transplantation (LT) is one of the most effective treatments for hepatocellular carcinoma (HCC). Although LT eliminates HCC and greatly reduces recurrence, some patients experience recurrence after LT. Criteria and models for screening patients with a high probability of HCC recurrence after LT, starting with the Milan criteria, have been published. These models have changed over time, but a standard has not been established. We summarized HCC prediction models after LT by focusing on the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 81 publications
2
15
0
Order By: Relevance
“…In our cohort study, we analyzed patients who were treated with TDF (n = 44) and ETV (n = 276) after LT for HBV-related HCC and found that TDF therapy was associated with a significantly lower risk of HCC recurrence than ETV treatment, which was observed in entire cohort, PSM cohort, beyond-MC cohort, multivariate analysis, competing risk analysis, subgroup analyses and sensitivity analyses. Other independent risk factors of HCC recurrence, such as microvascular invasion, were consistent with present studies [ 23 ]. In subgroup analyses (as Fig.…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort study, we analyzed patients who were treated with TDF (n = 44) and ETV (n = 276) after LT for HBV-related HCC and found that TDF therapy was associated with a significantly lower risk of HCC recurrence than ETV treatment, which was observed in entire cohort, PSM cohort, beyond-MC cohort, multivariate analysis, competing risk analysis, subgroup analyses and sensitivity analyses. Other independent risk factors of HCC recurrence, such as microvascular invasion, were consistent with present studies [ 23 ]. In subgroup analyses (as Fig.…”
Section: Discussionsupporting
confidence: 92%
“…MVI is the first step of intrahepatic tumor spread and distant metastasis of HCC, and is a known poor prognostic factor for HCC patients. [1][2][3][4][5][6][7][8][9][10][11]28,29 However, microscopically, there is a wide spectrum of MVI. Roayaie et al 13 reported that inva- sion of a vessel with a muscular wall can predict recurrence and survival among HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular invasion is one of the most significant prognostic factors of hepatocellular carcinoma (HCC) [1][2][3][4][5][6][7][8][9][10][11] and this parameter is consistently included in HCC staging systems, including the tumor-node-metastasis staging system used by the American Joint Committee on Cancer and the Barcelona Clinic Liver Cancer (BCLC) classification. 4,6,12 Vascular invasion can be classified into gross vascular invasion and microvascular invasion (MVI).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) and end-stage liver diseases have widely benefited from liver transplantation ( 125 , 126 ). However, HCC recurrence is one of the main causes of mortality in HCC patients who undergo liver transplantation ( 127 , 128 ). It has been established that certain tumor characteristics can lead to the recurrence of HCC, including the concentration of alpha fetoproteins, tumor diameter, macrovascular invasion, and extended orthotopic liver transplantation criteria ( 129 ).…”
Section: Nets and Hepatocellular Carcinoma Recurrencementioning
confidence: 99%